2007
DOI: 10.1007/s10584-007-9305-9
|View full text |Cite
|
Sign up to set email alerts
|

Some evidence of climate change in twentieth-century India

Abstract: The study of climate changes in India and search for robust evidences are issues of concern specially when it is known that poor people are very vulnerable to climate changes. Due to the vast size of India and its complex geography, climate in this part of the globe has large spatial and temporal variations. Important weather events affecting India are floods and droughts, monsoon depressions and cyclones, heat waves, cold waves, prolonged fog and snowfall. Results of this comprehensive study based on observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
176
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(190 citation statements)
references
References 16 publications
12
176
0
2
Order By: Relevance
“…Analysis of seasonal rainfall showed a decreasing trend in the monsoon season over India and increasing tendency during the pre-and post-monsoon months. Dash et al 5 and Kumar et al 4 did not find any significant trend in annual, seasonal and monthly rainfall. Interestingly, they observed decrease in annual and monsoon rainfall, and an increase in pre-monsoon, post-monsoon and winter rainfall over the years, on trend analysis using rainfall data for the country for 135 years (1871-2005); however, maximum increase in rainfall was observed during the pre-monsoon period.…”
Section: Literature Review -Rainfall Trends In Indiamentioning
confidence: 88%
See 2 more Smart Citations
“…Analysis of seasonal rainfall showed a decreasing trend in the monsoon season over India and increasing tendency during the pre-and post-monsoon months. Dash et al 5 and Kumar et al 4 did not find any significant trend in annual, seasonal and monthly rainfall. Interestingly, they observed decrease in annual and monsoon rainfall, and an increase in pre-monsoon, post-monsoon and winter rainfall over the years, on trend analysis using rainfall data for the country for 135 years (1871-2005); however, maximum increase in rainfall was observed during the pre-monsoon period.…”
Section: Literature Review -Rainfall Trends In Indiamentioning
confidence: 88%
“…No clear trend was observed while analysing the long period monsoon rainfall data particularly on all India scale. Some studies identified pockets of significant long-term rainfall changes 2,5,6 . Ramesh and Goswami 7 analysed daily gridded observed rainfall data for the period and found that the number of rainy days showed a decreasing trend.…”
Section: Literature Review -Rainfall Trends In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…They report that much of this observed trend is related to increases after Although, studies specific to the eastern Indian Himalaya are not available in the literature, many of the studies discussed above include the eastern Indian Himalaya as part of the greater northeast Indian region. For 1901-2003, Dash et al (2007 found a rise in Tmax of 1°C over the whole northeast India. The study reports annual average daily minimum temperature The Nepalese Himalaya also saw a warming trend in the last century.…”
Section: Strong Evidence Of Warmingmentioning
confidence: 96%
“…In a very recent regional study using Climate Research Unit's reconstructed temperature dataset (Brohan et al, 2006), Diodato et al (2011) show that in the last few decades the Himalayan and Tibetan Plateau region have warmed at a rate higher than that in the last century. They show a 0.5 °C in annual average maximum temperature (Tmax) warming over 1971compared to 1901-1960. Dash et al (2007 report that the western Indian Himalayas saw a 0.9 °C rise over 102 years .…”
Section: Strong Evidence Of Warmingmentioning
confidence: 98%